Exploring Strategic Decision Making In a Large Organisation - Stewart, David (School of Management Working Papers, 2011)
This paper explores strategic decision making in a large organisation. Utilizing postmodern narrative theory, stories were analysed using theme analysis and then placed on a paradigm grid to facilitate understanding of group decision making. In this paper the purely cognitive account of decision making is challenged as it fails to accommodate the personal motivation of decision makers and the political nature of many organisational decisions. The study also indicates that when decisions are made as a team, an integrator is needed to manage individual expectations. Finally the role of judgement in complex decision making where there is a high degree of uncertainty is explored and insights are gained into the practice of strategy.